Sex variant women in literature - Foster, Jeannette H.; Grier, Barbara (Tallahassee (Florida) : Naiad Press, 1985)
Fonds Suzan Daniel (FSD)
Met notenapparaat, bibliografieën, zakenregister
Engels
Monografie